An amino acid motif within the GABAA receptor alpha2 subunit promotes inhibitory synaptogenesis and seizure resilience. - Nathanson, Anna. (Tufts University. Tisch Library., 2019)
The efficacy of inhibitory neurotransmission is dependent on the accumulation of specific synaptic GABAA receptor (GABAAR) subtypes at the appropriate synaptic sites. To assess the role of a 15 amino acid motif found in the intracellular loop domain (ICD) of the GABAAR alpha2 subunit in selective inhibitory synaptogenesis, I generated a novel mouse model in which this alpha2 ICD motif has been knocked-in to the alpha1 subunit (Gabra1-2). This mutation leads to an enhanced in vivo interaction between the chimeric alpha1 subunit and the inhibitory synapse proteins collybistin and gephyrin and is sufficient to target alpha1-GABAARs to axo-axonic synapses at the axon initial segment. The Gabra1-2 mutation also constitutes an inhibitory synapse targeting motif, causing the over-accumulation of alpha1-GABAARs at synapses in the soma and dendrites, resulting in larger inhibitory synaptic currents. Gabra1-2 mice display an anxiolytic phenotype, alterations in baseline network oscillations, and decreased susceptibility to kainate-induced seizures. In addition, the Gabra1-2 mutation is able to rescue the spontaneous seizure and early postnatal death phenotype found in the previously described Gabra2-1 mouse, which lacks inhibitory synapses at the AIS. Taken together, my results demonstrate that the presence of the alpha2 ICD motif allows for subtype-selective binding of its GABAAR to collybistin and aggregation of the receptor in the inhibitory synaptic space. Increased synaptic clustering of the chimeric alpha1-GABAARs alters inhibitory neurotransmission and confers resilience to ictogenesis, demonstrating that manipulating the selective targeting of GABAAR subtypes may represent a novel therapeutic strategy to treat epilepsy.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Neuroscience.; Advisor: Stephen Moss.; Committee: Elif Engin, Jamie Maguire, Klaus Miczek, and Thomas Biederer.; Keyword: Neurosciences.